2007
DOI: 10.1111/j.1742-4658.2007.05981.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E‐derived antimicrobial peptide analogues with altered membrane affinity and increased potency and breadth of activity

Abstract: Host‐derived anti‐infective proteins represent an important source of sequences for designing antimicrobial peptides (AMPs). However such sequences are often long and comprise diverse amino acids with uncertain contribution to biological effects. Previously, we identified a simple highly cationic peptide derivative of human apolipoprotein E (apoEdp) that inhibited a range of microorganisms. Here, we have dissected the protein chemistry underlying this activity. We report that basic residues and peptide length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 50 publications
1
39
1
Order By: Relevance
“…The ApoEdpL-W antimicrobial peptide was previously shown to inhibit growth of both P. aeruginosa and S. aureus when added at micromolar concentrations on planktonic cultures (26). We tested the activity of ApoEdpL-W on planktonic and biofilm E. coli K-12 bacteria by using either strain MG1655 or its biofilm-forming isogenic derivative, MG1655 F= (37).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ApoEdpL-W antimicrobial peptide was previously shown to inhibit growth of both P. aeruginosa and S. aureus when added at micromolar concentrations on planktonic cultures (26). We tested the activity of ApoEdpL-W on planktonic and biofilm E. coli K-12 bacteria by using either strain MG1655 or its biofilm-forming isogenic derivative, MG1655 F= (37).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we investigated resistance mechanisms potentially induced by a new antimicrobial peptide derived from human apolipoprotein E, ApoEdpL-W. ApoEdpL-W is an aromatic-substituted peptide previously reported to be active against P. aeruginosa and S. aureus pathogens and to possibly interact with membranes (26). We showed that E. coli exposure to ApoEdpL-W induces Rcs, Cpx, and E pathways, three regulatory pathways known to sense envelope stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelly et al (35) recently described a series of peptides with low hemolytic activity and a broad spectrum of antimicrobial and antiviral activities. These peptides were derived from the receptor-binding region of human apolipoprotein E (ApoE), which has been shown to possess anti-infective properties (13).…”
mentioning
confidence: 99%
“…In addition, the lipidome composition of HCV particles has been shown to resemble that of VLDLs and LDLs (66), suggesting that CAMP is able to interact with HCV particles. Moreover, some AMPs are designed based on apolipoprotein sequences (67)(68)(69). This apparent cross talk between CAMP and apolipoproteins suggests that amphipathic ␣-helices from both proteins probably share the ability to bind to the same types of lipid membranes and induce similar curvature effects (70,71).…”
Section: Discussionmentioning
confidence: 99%